Knee fracture classification according to AO/OTA 2018 - Gordon, Max; Sköldenberg, Olof; Akbarian, Ehsan (AIDA Data Hub, 2021)
Test set used for knee fracture classification using the AO/OTA 2018 classification. 2472 images from 600 examinations. OpenAccess article available [here](https://doi.org/10.1371/journal.pone.0248809).
Keywords: Radiology; Computed radiography; Knee; Radiographs; Fractures; AO-classification; Medical and Health Sciences; Medicin och hälsovetenskap; Radiology and Medical Imaging; Radiologi och bildbehandling